Oesophageal atresia in the South West of England. - David, T J (1975)
A retrospective anatomical and family study was made of 345 patients with oesophageal atresia who were born in the South West of England between 1942 and 1973. There were 186 males and 159 females. Twenty-one cases were stillborn. Eighty-five percent of the patients had a combination of oesophageal atresia with a tracheo-oesophageal fistula to the distal oesophageal segment, and 9 percent had atresia without a fistula. Fifty-five per cent of the patients had other congenital malformations and these tended to be multiple rather than single. Thirty-six per cent of singletons had unequivocal fetal growth retardation, and there is some evidence that nearly all cases have poor fetal growth. There appeared to be a maternal age effect, with an excess of mothers under 20 and over 35, and there was an unexplained excess of fathers employed in the Armed Forces. Ten per cent of the cases were illegitimate. There were 21 twins which is nearly three times the expected number; there were two pairs of twins concordant for oesophageal atresia, one being monozygotic and the other dizygotic. In one case there were two sibs with oesophageal atresia. Five out of 365 sibs had anencephaly. The blood group distributions of the patients and their mothers did not significantly differ from the expected distribution. Oesophageal atresia is aetiologically heterogenous. In this series there were at least five, and probably 10 cases of trisomy 18 and four cases of trisomy 21. Five mothers had overt diabetes, and there is some suggestion from other work that maternal diabetes or its treatment may be aetiologically important. Oesophageal atresia was part of a possibly recessively inherited malformation syndrome in two cases. A sibship with a case of rectal atresia, a case of Hirschprung's disease and a case of oesophageal atresia may represent the action of another recessive gene. It seems likely that oesophageal atresia is a rather non-specific consequence of several teratological processes.